Development of polypeptide-based zwitterionic amphiphilic micelles for nanodrug delivery. Issue 31 (22nd July 2016) - Ma, Guanglong; Lin, Weifeng; Wang, Zhen; Zhang, Juan; Qian, Haofeng; Xu, Liangbo; Yuan, Zhefan; Chen, Shengfu
Abstract : Stable, protein molecules mimicking zwitterionic amphiphilic micelles based on polypeptides. Abstract : Protein molecules, which typically have a hydrophobic core and a zwitterionic shell with a polypeptide backbone, could be ideal materials for nanodrug vehicles (NDVs) with low side effects. Here, we synthesized poly(l -aspartic acid(lysine))- b -poly(l -lysine( Z )) (PAsp(Lys)- b -PLys( Z )) (PALLZ), a novel amphiphilic block polypeptide with key structures of protein to investigate the possibility for use as a NDV. This polypeptide can spontaneously self-assemble into micelles in aqueous solution with a zwitterionic brush (the PAsp(Lys) part) to provide the nonfouling shell and a hydrophobic core (the PLys( Z ) part) for loading hydrophobic drugs. The doxorubicin (DOX) loaded PALLZ micelles showed excellent resistance to nonspecific protein adsorption in FBS, which leads to very low internalization. Moreover, PALLZ micelles showed no cytotoxicity to MCF7, HeLa and HepG-2 cells up to 500 μg mL −1 . All these results indicated that zwitterionic amphiphilic block polypeptides could be promising materials for NDVs.